2017
DOI: 10.1116/1.5006670
|View full text |Cite
|
Sign up to set email alerts
|

Spatial atomic layer deposition for coating flexible porous Li-ion battery electrodes

Abstract: Ultrathin atomic layer deposition (ALD) coatings on the electrodes of Li-ion batteries can enhance the capacity stability of the Li-ion batteries. To commercialize ALD for Li-ion battery production, spatial ALD is needed to decrease coating times and provide a coating process compatible with continuous roll-to-roll (R2R) processing. The porous electrodes of Li-ion batteries provide a special challenge because higher reactant exposures are needed for spatial ALD in porous substrates. This work utilized a modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Trimethylaluminum/H 2 O Silicon photovoltaics [27] Al 2 O 3 2G glass Thermal, 100 Trimethylaluminum/O 3 OLED displays [32] Al 2 O 3 Porous LiCoO 2 Thermal, 60-120 Trimethylaluminum/O 3 Li-ion batteries [33] MoO 3 c-Si Plasma, 120 (NtBu) 2 (NMe 2 ) 2 Mo/O 2 Silicon photovoltaics Pt TiO 2 P25 nanoparticles Thermal, 100 MeCpPtMe 3 /O 2 Photocatalysis [34] TiO 2 Glass/ITO Thermal, 100 Titanium terachloride/H 2 O Organic photovoltaics [35] Al-doped ZnO c-Si, borosilicate glass Thermal, 220 Diethylzinc/H 2 O/trimethylaluminum Silicon photovoltaics [36] ZnO Borosilicate glass Thermal, 200 Diethylzinc/H 2 O Transistors [37] ZnO Perovskite Thermal, 95 Diethylzinc/H 2 O Perovskite photovoltaics [38] Figure 1. Schematic diagram of the spatial ALD reactor used in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Trimethylaluminum/H 2 O Silicon photovoltaics [27] Al 2 O 3 2G glass Thermal, 100 Trimethylaluminum/O 3 OLED displays [32] Al 2 O 3 Porous LiCoO 2 Thermal, 60-120 Trimethylaluminum/O 3 Li-ion batteries [33] MoO 3 c-Si Plasma, 120 (NtBu) 2 (NMe 2 ) 2 Mo/O 2 Silicon photovoltaics Pt TiO 2 P25 nanoparticles Thermal, 100 MeCpPtMe 3 /O 2 Photocatalysis [34] TiO 2 Glass/ITO Thermal, 100 Titanium terachloride/H 2 O Organic photovoltaics [35] Al-doped ZnO c-Si, borosilicate glass Thermal, 220 Diethylzinc/H 2 O/trimethylaluminum Silicon photovoltaics [36] ZnO Borosilicate glass Thermal, 200 Diethylzinc/H 2 O Transistors [37] ZnO Perovskite Thermal, 95 Diethylzinc/H 2 O Perovskite photovoltaics [38] Figure 1. Schematic diagram of the spatial ALD reactor used in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The precursor exposure time was defined by the rotation speed of the inner drum upon which the samples resided as it moved through precursor dosing zones. The two rotation speeds used in this work, 0.5 and 5 rpm, correspond to exposure times of 6 and 0.6 s …”
Section: Experimental Methodsmentioning
confidence: 99%
“…[ 255 ] For example, Mousa et al through theoretical modeling reported that the precursor gas flow rates, the distance between the substrate and reactor surfaces, and channel spacing impacts the conformality and quality of material deposition in SALD. [ 256 ] In recent times, SALD has also been employed to deposit materials for various applications such as ZnO in thin film Li‐ion batteries, [ 257 ] SnO x in perovskite solar cell, [ 258 ] Al 2 O 3 as moisture barrier coating, [ 259 ] and MoO x as charge selective layer in Si solar cell. [ 260 ] Similarly, close‐proximity SALD has been employed commercially by companies such as Levitech and SoLayTec to deposit Al 2 O 3 thin films on Si solar cells for surface passivation.…”
Section: Emerging Technologiesmentioning
confidence: 99%